Research on Brand Visual Packaging Design based on Interestingness and Emotion - Wang, Beibei (Transactions on Social Science, Education and Humanities Research, 2023)
In today’s competitive environment of packaging market, the homogenization of packaging brands is serious, and it is difficult for packaging to stand out in front of consumers. In order to highlight the brand and improve its competitiveness, brand packaging also needs to meet the emotional needs of consumers and enhance the attractiveness and recognition of brand packaging design to consumers. Through the brief introduction of the theory of interesting and emotional brand visual packaging design and the analysis and comparison of different brands’ visual packaging design cases in the market, the importance of interesting emotional design to brand packaging is proved. In the meantime, through the conceptual brand packaging design, consumers can have a sense of identity in the brand design with consistent values so as to achieve emotional resonance. Based on the theoretical research of design science and psychology, four brand packaging design strategies are put forward and a practical design of sanitary napkin brand packaging is made. This paper summarizes the application and importance of interesting emotional design, brand vision, and material innovation in brand packaging design, and shows that the interesting and emotional brand visual packaging design can resonate with consumers and be forward-looking in the future brand design field. Moreover, this study provides a new idea for the development of interesting and emotional brand vision and how to promote the development of brand packaging design such as green design.